Scalable and Highly Efficient Mesoporous Wood‐Based Solar Steam Generation Device: Localized Heat, Rapid Water Transport. (21st February 2018) - Li, Tian; Liu, He; Zhao, Xinpeng; Chen, Guang; Dai, Jiaqi; Pastel, Glenn; Jia, Chao; Chen, Chaoji; Hitz, Emily; Siddhartha, Das; Yang, Ronggui; Hu, Liangbing
Abstract: Solar steam generation is regarded as one of the most sustainable techniques for desalination and wastewater treatment. However, there has been a lack of scalable material systems with high efficiency under 1 Sun. A solar steam generation device is designed utilizing crossplane water transport in wood via nanoscale channels and the preferred thermal transport direction is decoupled to reduce the conductive heat loss. A high steam generation efficiency of 80% under 1 Sun and 89% under 10 Suns is achieved. Surprisingly, the crossplanes perpendicular to the mesoporous wood can provide rapid water transport via the pits and spirals. The cellulose nanofibers are circularly oriented around the pits and highly aligned along spirals to draw water across lumens. Meanwhile, the anisotropic thermal conduction of mesoporous wood is utilized, which can provide better insulation than widely used super‐thermal insulator Styrofoam (≈0.03 W m −1 K −1 ). The crossplane direction of wood exhibits a thermal conductivity of 0.11 W m −1 K −1 . The anisotropic thermal conduction redirects the absorbed heat along the in‐plane direction while impeding the conductive heat loss to the water. The solar steam generation device is promising for cost‐effective and large‐scale application under ambient solar irradiance. Abstract : A low‐cost steam generation device is demonstrated with 80% conversion efficiency under 1 Sun. The heat transfer and fluidic transport directions are decouple, utilizing the mesostructure of wood. The anisotropic thermal conduction redirects the absorbed heat in‐plane while impeding heat loss into bulk water. Nanoscale pits and spirals in crossplanes function as efficient water supply channels.